Determination of Passenger Car Unit and Capacity Loss at Curve Section of Two-Lane Undivided Highway: A Case Study of Balkhu-Chovar-Dakshinkali Road Section - K.C., Tuphan Jijung; Shahi, Thusitha Chandani (Journal on Transportation System and Engineering, 2025)
Passenger Car Units (PCU) serve as a crucial metric in assessing the impact of different vehicle types on traffic flow, particularly in heterogeneous, non-lane-based traffic conditions prevalent on Nepal’s two-lane undivided highways. Factors such as lane width, horizontal alignment, gradient, lateral clearance, and shoulder conditions significantly influence PCU values and roadway capacity. However, the specific effect of horizontal curve radius on PCU estimation and capacity loss remains largely unexplored in Nepalese road conditions. This study investigates the influence of horizontal curve radius on PCU values and roadway capacity along the Balkhu-Chovar-Dakshinkali highway using videographic traffic surveys. Speed-flow-density relationships were established using Greenshield’s model, and the dynamic PCU method was applied to estimate PCU values based on speed variations and projected vehicle areas. The findings indicate that PCU values increase with curve radius, with heavy vehicles, such as buses and trucks, exhibiting more significant changes than light vehicles. Specifically, PCU values for buses ranged from 5.2986 to 5.4333, and for trucks from 3.3743 to 3.4450, as the curve radius expanded from 32m to 151m. Additionally, capacity loss was found to decrease as the curve radius increased, with a 25.27% reduction at a 32m radius and 7.92% at a 151m radius. The maximum roadway capacity at the Chovar straight section was found to be 1451 PCU/hr per lane, which is lower than the 1600 PCU/hr per lane suggested by the Indian Highway Capacity Manual (HCM) for hilly terrain. These results emphasize the significant impact of horizontal curvature on heavy vehicles and highlight the necessity for curve-specific PCU estimation and geometric design improvements to minimize capacity loss and optimize roadway performance on hilly terrain highways.